MioC and GidA proteins promote cell division in E. coli - Lies, Mark; Visser, Bryan J.; Joshi, Mohan C.; Magnan, David; Bates, David (Frontiers in Microbiology, 2015)
The well-conserved genes surrounding the E. coli replication origin, mioC and gidA, do not affect chromosome replication and have little known function. We report that mioC and gidA mutants exhibit a mild cell division inhibition phenotype, which is exacerbated by a fis deletion. Measurements replication initiation frequency, replication elongation, and chromosome segregation indicate that cell division inhibition does not involve any effects of these genes on oriC function. Division inhibition is independent of the major cell division control systems including the SOS response and nucleoid occlusion. Complementation analysis indicates that mioC and gidA affect cell division in trans, and transcriptome analysis by next-generation RNA sequencing showed that expression of a cell division septum component, YmgF, is strongly affected in both mioC and gidA mutants. Our results suggest that MioC and GidA proteins are involved in a cell division regulatory pathway, which may link DNA replication and division.